Crank length alters kinematics and kinetics, yet not the economy of recumbent handcyclists at constant handgrip speeds - Mason, B. S.; Stone, B.; Warner, M. B.; Goosey-Tolfrey, V. L. (Scandinavian Journal of Medicine & Science in Sports, 2021)
Handcycling performance is dependent on the physiological economy of the athlete; however, handbike configuration and the biomechanical interaction between the two are also vital. The purpose of this study was to examine the effect of crank length manipulations on physiological and biomechanical aspects of recumbent handcycling performance in highly trained recumbent handcyclists at a constant linear handgrip speed and sport-specific intensity. Nine competitive handcyclists completed a 3-minute trial in an adjustable recumbent handbike in four crank length settings (150, 160, 170 & 180 mm) at 70% peak power output. Handgrip speed was controlled (1.6 m·s-1) across trials with cadences ranging from 102 to 85 rpm. Physiological economy, heart rate, and ratings of perceived exertion were monitored in all trials. Handcycling kinetics were quantified using an SRM (Schoberer Rad Messtechnik) powermeter, and upper limb kinematics were determined using a 10-camera VICON motion capture system. Physiological responses were not significantly affected by crank length. However, greater torque was generated (P < .0005) and peak torque occurred earlier during the push and pull phase (P = .001) in longer cranks. Statistical parametric mapping revealed that the timing and orientation of shoulder flexion, shoulder abduction, and elbow extension were significantly altered in different crank lengths. Despite the biomechanical adaptations, these findings suggest that at constant handgrip speeds (and varying cadence) highly trained handcyclists may select crank lengths between 150 and 180 mm without affecting their physiological performance. Until further research, factors such as anthropometrics, comfort, and self-selected cadence should be used to facilitate crank length selection in recumbent handcyclists.